2019
DOI: 10.1142/s0218127419300210
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction Dynamics Induces Localized Conductance Bistability in Cardiac Tissue

Abstract: Connexins are specialized ionic channels that control the action potential propagation between cardiac myocytes. In this paper, we study the connexin dynamics in a one-dimensional model of cardiac tissue. We show that the connexin dynamics may lead to a spatial organization of the gap junction conductance. In the numerical simulations presented in this paper we have found two different regimes for the spatial organization of the conductances: (a) a spatially uniform conductance; (b) a spatially complex pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…15 Here, we have reproduced this dynamical uncoupling at long time scales. Furthermore, we have used a simplified description with a low number of cells to relate the uncoupling to the existence of multistability, thus explaining the previously observed effect 24 of the emergence at a long time scale of a very disordered state with inhomogeneous intercellular conductances. The effect on the action potential conduction velocity of the heterogeneities in the conductance distribution has also been addressed.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…15 Here, we have reproduced this dynamical uncoupling at long time scales. Furthermore, we have used a simplified description with a low number of cells to relate the uncoupling to the existence of multistability, thus explaining the previously observed effect 24 of the emergence at a long time scale of a very disordered state with inhomogeneous intercellular conductances. The effect on the action potential conduction velocity of the heterogeneities in the conductance distribution has also been addressed.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it is due to a pre-existing heterogeneity of the medium. In a recent publication, 24 we observed that the dispersion in velocity might appear in an utterly homogeneous tissue due to the voltage and time dependence of the intercellular conductance. In the present paper, we will further extend the analysis of the spatially dependent conductances and provide a stability analysis of the mathematical model.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations